Gingerols and shogaols: Important nutraceutical principles from ginger. (September 2015) - Semwal, Ruchi Badoni; Semwal, Deepak Kumar; Combrinck, Sandra; Viljoen, Alvaro M.
Graphical abstract: Gingerols and the corresponding shogaols are the major pungent compounds present in the rhizomes of fresh and dried ginger ( Zingiber officinale ), respectively. The compounds have a favourable toxicity profile, but are cytotoxic towards a range of cancer cell lines. Tumours induced in several animal models were successfully treated by gingerols. Highlights: Ginger is a reputed folk remedy used to treat a range of disorders. Gingerols display various nutraceutical benefits including counteracting obesity and diabetes. Malignant tumours were successfully treated by gingerols in animal models. Ginger metabolites have a favourable toxicity profile. Abstract: Gingerols are the major pungent compounds present in the rhizomes of ginger ( Zingiber officinale Roscoe) and are renowned for their contribution to human health and nutrition. Medicinal properties of ginger, including the alleviation of nausea, arthritis and pain, have been associated with the gingerols. Gingerol analogues are thermally labile and easily undergo dehydration reactions to form the corresponding shogaols, which impart the characteristic pungent taste to dried ginger. Both gingerols and shogaols exhibit a host of biological activities, ranging from anticancer, anti-oxidant, antimicrobial, anti-inflammatory and anti-allergic to various central nervous system activities. Shogaols are important biomarkers used for the quality control of many ginger-containing products, due to their diverse biological activities. In this review, a large body of available knowledge on the biosynthesis, chemical synthesis and pharmacological activities, as well as on the structure–activity relationships of various gingerols and shogaols, have been collated, coherently summarised and discussed. The manuscript highlights convincing evidence indicating that these phenolic compounds could serve as important lead molecules for the development of therapeutic agents to treat various life-threatening human diseases, particularly cancer. Inclusion of ginger or ginger extracts in nutraceutical formulations could provide valuable protection against diabetes, cardiac and hepatic disorders.